Export-deficient monoubiquitinated PEX5 triggers peroxisome removal in SV40 large T antigen-transformed mouse embryonic fibroblasts - Nordgren, M (2015)
Peroxisomes are ubiquitous cell organelles essential for human health. To maintain a healthy cellular environment, dysfunctional and superfluous peroxisomes need to be selectively removed. Although emerging evidence suggests that peroxisomes are mainly degraded by pexophagy, little is known about the triggers and molecular mechanisms underlying this process in mammalian cells. In this study, we show that PEX5 proteins fused to a bulky C-terminal tag trigger peroxisome degradation in SV40 large T antigen-transformed mouse embryonic fibroblasts. In addition, we provide evidence that this process is autophagy-dependent and requires monoubiquitination of the N-terminal cysteine residue that marks PEX5 for recycling. As our findings also demonstrate that the addition of a bulky tag to the C terminus of PEX5 does not interfere with PEX5 monoubiquitination but strongly inhibits its export from the peroxisomal membrane, we hypothesize that such a tag mimics a cargo protein that cannot be released from PEX5, thus keeping monoubiquitinated PEX5 at the membrane for a sufficiently long time to be recognized by the autophagic machinery. This in turn suggests that monoubiquitination of the N-terminal cysteine of peroxisomeassociated PEX5 not only functions to recycle the peroxin back to the cytosol, but also serves as a quality control mechanism to eliminate peroxisomes with a defective protein import machinery.